Australian Marsh Beetles (Coleoptera: Scirtidae). 8. The new genera Cygnocyphon, Eximiocyphon, Paracyphon, Leptocyphon, Tectocyphon, and additions to Contacyphon de Gozis, Nanocyphon Zwick and Eurycyphon Watts - Zwick, Peter (Zootaxa, 2015)
New monotypic genera proposed are: Cygnocyphon ibex n. gen., n. sp., Eximiocyphon excisus n. gen., n. sp., and Paracyphon avicularis n. gen., n. sp. Also proposed are the new genera Leptocyphon n. gen., with L. furcalonga, n. sp. and L. quadricornutus, n. sp., Tectocyphon n. gen., with T. microphallus n. sp., T. hirsutus n. sp., and T. victoriae n. sp. The diagnosis of genus Eurycyphon Watts is amended, E. fulvus Watts and E. aquilus Watts are partly redescribed. New species are: Eurycyphon barringtoni n. sp., E. castaneus n. sp., E. falcatus n. sp., E. parvus n. sp., E. perlatus n. sp., E. thunguttii, n. sp., E. tomweiri n. sp., and E. tricornis n. sp. Species of Nanocyphon are discussed and N. tasmanicus n. sp. is described. Contacyphon forcipatus n. sp. is described and an apparently introduced population of the European Contacyphon putonii Gozis is reported from West Australia. For comparison with some of the new taxa the redescription of Pseudomicrocara orientalis Armstrong, type species of the genus, is supplemented.